Comparison of the effect of intrathecal fentanyl citrate and magnesium sulfate as adjuvants to hyperbaric levobupivacaine 0.5% for spinal anesthesia in patients undergoing lower limb orthopedic surgeries - Tripathy, Anusha; Tandon, Neelima; Jain, Namrata; Singh, Devendra (Asian Journal of Medical Sciences, 2024)
Background: Subarachnoid blockade is a safe, reliable, and inexpensive technique that provides surgical anesthesia along with prolonged post-operative analgesia. The quality of subarachnoid block is enhanced by the addition of intrathecal adjuvants, such as fentanyl citrate and magnesium sulfate to hyperbaric levobupivacaine. Aims and Objectives: The aim of this study was to compare the effects of fentanyl and magnesium sulfate as adjuvants to 0.5% hyperbaric levobupivacaine in orthopedic surgeries under subarachnoid block. Materials and Methods: This prospective randomized study included 90 American Society of Anesthesiologists Grade I and II patients aged 18–60 years undergoing orthopedic surgeries. Group LS received 3 mL 0.5% levobupivacaine heavy+0.5 mL normal saline. Group LF received 3 mL 0.5% levobupivacaine heavy+fentanyl 25 μg, and Group LM, 3 mL 0.5% levobupivacaine heavy+magnesium sulphate 50 mg+0.4 mL normal saline. The onset and duration of sensory and motor block and intraoperative hemodynamics were recorded. In the post-operative period, duration of analgesia, Visual Analog Scales scores, and side effects were observed. Results: The onset of sensory block was 4.04±0.74 min in Group LM (P<0.001) as compared to Groups LF (2.01±0.23 min) and LS (2±0.24 min). The onset of motor blockade took 5±1.14 min in the control group, 7.01±0.94 in group LF, and 8.11±1.33 min in group LM (P<0.001). The duration of analgesia in group LS was 183.73±12.08 min, 317±18.6 min in group LF, and 219.43±20.89 in group LM (P<0.001). Conclusion: The addition of fentanyl and magnesium as adjuvants enhanced the quality of subarachnoid block when added to hyperbaric levobupivacaine. The duration of analgesia was longest in fentanyl, followed by magnesium and then control. The incidence of side effects was greatest in fentanyl, followed by control and nil in magnesium.